2014
DOI: 10.1155/2014/139314
|View full text |Cite
|
Sign up to set email alerts
|

Different Approximations to the Solution of Upper-Convected Maxwell Fluid over a Porous Stretching Plate

Abstract: In the present paper, we consider an incompressible magnetohydrodynamic flow of two-dimensional upper-convected Maxwell fluid over a porous stretching plate with suction and injection. The nonlinear partial differential equations are reduced to an ordinary differential equation by the similarity transformations and taking into account the boundary layer approximations. This equation is solved approximately by means of the optimal homotopy asymptotic method (OHAM). This approach is highly efficient and it contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…For p ∈ [0, 1] an embedding parameter and X an analytic function, we propose to construct a homotopy [29][30][31][32][33][34][35][36]:…”
Section: Basic Ideas Of the Optimal Homotopy Asymptotic Methodsmentioning
confidence: 99%
“…For p ∈ [0, 1] an embedding parameter and X an analytic function, we propose to construct a homotopy [29][30][31][32][33][34][35][36]:…”
Section: Basic Ideas Of the Optimal Homotopy Asymptotic Methodsmentioning
confidence: 99%
“…whereB 0 ðtÞ denotes the applied magnetic field. The theological model that illustrates the Sisko fluid [39][40][41][42][43] asT…”
Section: Problem Formulationmentioning
confidence: 99%
“…Sar et al 42 have been described boundary layer equations of Sisko fluid. Marinca et al 43 have studied Maxwell fluid flow through a porous stretching plates. Moallemi et al 44 have found an exact solution for Sisko fluid flow in a pipe.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the optimal homotopy asymptotic method (OHAM) [12][13][14][15][16] is applied to obtain accurate, effective analytic approximate solutions. The quality of the approximate solutions is investigated using two important statistical tests: the Bartlett test and the Durbin-Wattson test.…”
Section: Introductionmentioning
confidence: 99%